Potensi Spirulina Platensis Sebagai Sumber Kosmetik - Betaria Sonata Sianturi; Inda Vandiwinata Simaremare; Siti Aisyah; Yosa Martini Gultom; Dortua Marbun; Ivo Elsa samaria Hutabarat; Servina Indah Yani Tarigan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Spirulina Platensis, a type of blue-green algae, has attracted the attention of the cosmetics industry due to its extraordinary nutritional and antioxidant properties. This microalgae is rich in vitamins, minerals, and amino acids, making it an attractive ingredient for skin care products. Methods used. The qualitative literature review research method is an approach used to collect, evaluate, and synthesize existing studies in the relevant scientific literature. with a specific topic. Based on research results, Spirulina platensis has great potential as a cosmetic ingredient that can provide benefits in caring for and protecting the skin. However, consult a medical professional or esthetician before using products containing Spirulina platensis.